STUDI DESKRIPTIF TENTANG KESABARAN IBU BEKERJA DALAM MENGASUH ANAK HIPERAKTIF DI SDN PUTRACO-INDAH - Lisa W; Kintan M; Andhini F; Risha W (Psympathic : Jurnal Ilmiah Psikologi, 2015)
Each parent was given a great responsibility, extraordinary privilege and grace as a role model that determines life, perhaps even growing someone who someday will become parents too. For working mothers, they are required to be able to divide their time between work and family time. In a phenomenon that we have encountered, working mother and have a hyperactive child often experience stress. This is caused by the condition of the mother when went home after office are facing some difficulties in controlling their child behavior. For that it takes the patience of a mother in particular who work in raising children are hyperactive so that later the child can maximize his or her potential.